Implementasi Manajemen Kurikulum Pondok Pesantren Al-Masthuriyah - Badrudin, Badrudin; Munaya, Amira; Arul, Arul (El-Idare, 2023)
Curriculum management in Islamic boarding school education is known for relying on traditional curriculum management and avoiding modern educational curricula. The aim of this research is to investigate the planning, implementation, and evaluation of the curriculum at Al-Masturiyah Islamic Boarding School in Sukabumi Regency. This research adopts a qualitative approach with a case study on Al-Masthuriyah Boarding School, focusing on curriculum management implementation. This approach allows for a deep understanding of the context, processes, and impact of curriculum management in the boarding school. Involving the head of the school, teachers, students, and parents as informants, data collection techniques include in-depth interviews, participatory observation, and document analysis. Data analysis techniques include data reduction, data display, and verification. The findings indicate that the school's curriculum integrates Quranic teachings, traditional texts, and extracurricular activities, emphasizing not only academic education but also character development and talents. Evaluation involves written and oral exams, along with evaluation conferences for school development. Graduation standards emphasize virtuous character, illustrating a holistic approach to student assessment.